2017
DOI: 10.1128/mbio.00503-17
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Toxin-Derived Peptides Destabilize and Inactivate Clostridium difficile TcdB

Abstract: Clostridium difficile infection (CDI) is a major cause of hospital-associated, antibiotic-induced diarrhea, which is largely mediated by the production of two large multidomain clostridial toxins, TcdA and TcdB. Both toxins coordinate the action of specific domains to bind receptors, enter cells, and deliver a catalytic fragment into the cytosol. This results in GTPase inactivation, actin disassembly, and cytotoxicity. TcdB in particular has been shown to encode a region covering amino acids 1753 to 1851 that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Treatment with TcdB2 Δ1773-1774 and TcdB2 Δ2213-2223 or TcdB2 alone resulted in an EC 50 of between 10 and 100 fM. Of the mutants tested, only cells treated with TcdB2 Δ1769 -1787 , the deletion region corresponding to TcdB-derived inhibitory peptide PepB2 (16), showed no loss of cell viability at the highest concentration tested. This observation held true even when cells were exposed to TcdB2 Δ1769 -1787 at a final concentration of 1 M (data not shown).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Treatment with TcdB2 Δ1773-1774 and TcdB2 Δ2213-2223 or TcdB2 alone resulted in an EC 50 of between 10 and 100 fM. Of the mutants tested, only cells treated with TcdB2 Δ1769 -1787 , the deletion region corresponding to TcdB-derived inhibitory peptide PepB2 (16), showed no loss of cell viability at the highest concentration tested. This observation held true even when cells were exposed to TcdB2 Δ1769 -1787 at a final concentration of 1 M (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…The TcdB2 deletion mutant retains glucosylation activity. Previous work has suggested that the efficiency of glucosylation of TcdA and TcdB is hindered by conformational restrictions within the proteins (16,20). It was therefore predicted that deletions which remove conformational constraints in TcdB could result in forms of the protein with altered glucosylation activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations